PENYEDIAAN SAYURAN SEGAR KEMASAN SIAP OLAH UNTUK KONSUMSI RUMAH TANGGA KADER KESEHATAN KELURAHAN BANDUNG KOTA TEGAL GUNA MENINGKATKAN IMUN DI MASA PANDEMI - Deddy Utomo; Anny Fauziyah; Agus Mulyadi; Nurcholis Nurcholis (Jurnal Inovasi Masyarakat Terupdate, 2024)
Background Vegetables are very important nutrients for the body. Vegetables are a source of vitamins, minerals and fiber which function as antioxidants. A person who consumes vegetables according to the WHO daily allowance will increase the body's immunity/stamina so that it is resistant to exposure to infection. In the long term. The level of community vegetable consumption is still low, 95.5% of Indonesian people are reported to consume vegetables below the standards set by WHO. One of the factors that influences increasing vegetable consumption is the availability of easily accessible vegetables. The aim is to increase adequate vegetable consumption for health workers and health cadres who are always involved in health management efforts. The community service method used is providing education and providing ready-to-process packaged vegetables which are useful for increasing body immunity for health cadres from Bandung Village, Tegal City. Service results after being educated about vegetable knowledge rose from 6.6 points to 8.5 points. All participants who took part in community service activities stated that after being given packaged vegetable packages, they gained the experience that vegetable packages were very easy to process and serve, their body condition became healthier, and processing was very fast and easy.